Hepatocyte growth factor, colony-stimulating factor 1, CD40, and 11 other inflammation-related proteins are associated with pain in diabetic neuropathy: exploration and replication serum data from the Pain in Neuropathy Study. Issue 5 (24th May 2022) - Bäckryd, Emmanuel; Themistocleous, Andreas; Larsson, Anders; Gordh, Torsten; Rice, Andrew S.C.; Tesfaye, Solomon; Bennett, David L.; Gerdle, Björn
Abstract : Supplemental Digital Content is Available in the Text. In a subgroup of patients with diabetic polyneuropathy, the severity of neuropathy and neuropathic pain were associated with high levels of systemic inflammatory biomarkers. Abstract: One in 5 patients with diabetes suffers from chronic pain with neuropathic characteristics, but the pathophysiological mechanisms underlying the development of neuropathic pain in patients with diabetic distal symmetrical polyneuropathy (DSP) are poorly understood. Systemic low-grade inflammation has been implicated, but there is still a considerable knowledge gap concerning its scope and meaning in this context. The aim of the study was to establish the broad inflammatory signature of painful diabetic DSP in serum samples from the Pain in Neuropathy Study, an observational cross-sectional multicentre study in which participants underwent deep phenotyping. In the present two cohorts exploration–replication study (180 participants in each cohort), serum samples from Pain in Neuropathy Study participants were analyzed with the Olink INFLAMMATION panel (Olink Bioscience, Uppsala, Sweden) that enables the simultaneous measurement of 92 inflammation-related proteins (mainly cytokines, chemokines, and growth factors). In both the exploration and the replication cohort, we identified a high-inflammation subgroup where 14 inflammation-related proteins in particular were associated with more neuropathy and higher pain intensity. The top 3 proteins were hepatocyte growth factor, colony-stimulating factor 1, and CD40 in both cohorts. In the exploratory cohort, additional clinical data were available, showing an association of inflammation with insomnia and self-reported psychological distress. Hence, this cross-sectional exploration–replication study seems to confirm that low-grade systemic inflammation is related to the severity of neuropathy and neuropathic pain in a subgroup of patients with diabetic DSP. The pathophysiological relevance of these proteins for the development of neuropathic pain in patients with diabetic DSP must be explored in more depth in future studies.